2007
DOI: 10.1139/z07-001
|View full text |Cite
|
Sign up to set email alerts
|

Litter size, sex ratio, and age structure of gray wolves, Canis lupus, in relation to population fluctuations in northern Belarus

Abstract: Gray wolf (Canis lupus L., 1758) population fluctuations in northern Belarus (Vitebsk region) between 1990 and 2003 were significantly affected by hunting pressure by humans. Mean litter size was inversely density dependent and varied from 4.8 to 7.7 pups (range 2-10). The increase in litter size with declining density of wolf population concerned only female pups, whereas the number of male pups in a litter was not related to population density. The sex ratio of pups varied significantly: the proportion of fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 15 publications
1
22
0
1
Order By: Relevance
“…Our results might indicate a population-level response to territory vacancies and per capita food availability. Similar inversely density-dependent effects have been reported for grey wolf Canis lupus, with litter sizes increasing with declining density due to higher availability of food (Rausch, 1967;Sidorovich, Tikhomirova & Jedrzejewska, 2003;Sidorovich et al, 2007).…”
Section: Discussionsupporting
confidence: 76%
“…Our results might indicate a population-level response to territory vacancies and per capita food availability. Similar inversely density-dependent effects have been reported for grey wolf Canis lupus, with litter sizes increasing with declining density due to higher availability of food (Rausch, 1967;Sidorovich, Tikhomirova & Jedrzejewska, 2003;Sidorovich et al, 2007).…”
Section: Discussionsupporting
confidence: 76%
“…The average age of tundra–taiga wolves in our study (2·0 years) was intermediate to the average ages of 1·5 and 2·8 years reported in a comparable study during periods of high and low hunting pressure, respectively (Sidorovich et al . ). Similarly, the proportion of tundra–taiga wolves <1 year old in our study (39%) was intermediate to proportions of 55% and 34% reported during periods of high and low hunting (Sidorovich et al .…”
Section: Discussionmentioning
confidence: 97%
“…Similarly, the proportion of tundra–taiga wolves <1 year old in our study (39%) was intermediate to proportions of 55% and 34% reported during periods of high and low hunting (Sidorovich et al . ). This comparison suggests that tundra–taiga wolves could have a skewed age structure and higher proportion of juveniles relative to populations with lower hunting pressure.…”
Section: Discussionmentioning
confidence: 97%
“…Yet, in our case study, the sex ratio obtained from camera traps was closer to 1 M:1 F than the sex ratio obtained from genetic identification (2.7 M:1 F). The sex ratio is alleged to be close to one (Kreeger 2003), even though there is some evidence of a possible bias towards males in adult wolves (Mech 1970) or towards female pups in low-density populations (Sidorovich et al 2007). A slight prevalence of male genotypes has been detected in other NGS studies in Italy Marucco et al 2009).…”
Section: Discussionmentioning
confidence: 98%